ANALYSIS OF THE CHEMICAL CONTENT OF HAIRY COCKLE (Anadara antiquata)MEAT - Sayyidina Ahmad Zhariif; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTShellfish is one of the soft animals (Mollusca) class Bivalvia or Pelecypoda. The shells used in this study are shells fleeceare widely used as an alternative food source. This study aims to determine the chemical content of shell fleece. The research method is an experimental method  in 2 stages, namely the preparation of samples of shell fleece and analysis of the chemical composition of shell fleece. Chemical composition analysis parameters consist of moisture, ash, fat, and protein content. The resultsshowed that the chemical content of shell fleece was 79% (ww), ash content 9.24% (dw), protein 45.52% (dw), and fat 36.08% (dw). Keywords: chemical of compotition, mollusca, protein